2014
DOI: 10.1364/oe.22.024411
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative technique for robust and noise-tolerant speed measurements based on speckle decorrelation in optical coherence tomography

Abstract: Abstract:Intensity-based techniques in optical coherence tomography (OCT), such as those based on speckle decorrelation, have attracted great interest for biomedical and industrial applications requiring speed or flow information. In this work we present a rigorous analysis of the effects of noise on speckle decorrelation, demonstrate that these effects frustrate accurate speed quantitation, and propose new techniques that achieve quantitative and repeatable measurements. First, we derive the effect of backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 33 publications
0
64
0
Order By: Relevance
“…(9) into diffusional and translational averages [2, 9]. The diffusional average ν,χ=1Nnormalei2nkc[zν(τ)-zχ(0)] cancels out for ν ≠ χ and its value is ν=1Nnormalei2nkc[zν(τ)-zν(0)]=e-4n2kc2Dτ, where D is the diffusion coefficient and we define now kD=2n2kc2D [9, 13]. It is important to note here that if the scattering is produced by non-spherical particles other sources of diffusive decorrelation need to be taken into account.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) into diffusional and translational averages [2, 9]. The diffusional average ν,χ=1Nnormalei2nkc[zν(τ)-zχ(0)] cancels out for ν ≠ χ and its value is ν=1Nnormalei2nkc[zν(τ)-zν(0)]=e-4n2kc2Dτ, where D is the diffusion coefficient and we define now kD=2n2kc2D [9, 13]. It is important to note here that if the scattering is produced by non-spherical particles other sources of diffusive decorrelation need to be taken into account.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Several applications of the DLS-OCT technique have been actively discussed recently [812], including a derivative technique that uses only the intensity of the OCT signal. Termed intensity-based DLS-OCT (iDLS-OCT) [13], this approach extends DLS methods to a broader range of wavelength-swept OCT systems that lack phase stability [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is known that the assessment of the physiological significance of stenotic coronary lesions, through estimations of flow impairment, can be an important method for determining optimum intervention. Recent work has suggested that direct flow measurements can be made directly from the OCT data, potentially enhancing the diagnostic information gained by intravascular imaging [113][114][115]. Other studies have suggested a potential role of OCT for monitoring atrial ablation [116][117][118].…”
Section: Discussionmentioning
confidence: 99%
“…We successfully demonstrated adaptive motion tracking using XCC that maximized. On the other hand, XCC measurement that suffers from uncertainty that can be quantified by σ xcc (standard deviation) [30]. An alternative strategy is to perform speckle tracking using XCC values that optimize the ratio between S and σ xcc : (η = S/σ xcc ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%